2018
DOI: 10.1177/1708538118811483
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistulas ipsilateral to internal jugular catheters for hemodialysis have decreased patency rates

Abstract: Purpose This study aimed to evaluate the effects of hemodialysis catheters on the survival of subsequent arteriovenous fistulas, according to the relative localization to the catheters. Methods A total of 201 patients who initiated dialysis therapy using a hemodialysis catheter were eligible for this retrospective study. Arteriovenous fistulas were created on the nondominant upper extremity after the placement of hemodialysis catheters. The catheters were removed after four consecutive successful dialyses via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In one previous retrospective study of 322 patients, it was noted that AVF survival was lower in those with ipsilateral TVCs compared with contralateral TVCs, but the primary AVF failure rates were similar (50% vs 53%, P =0.70) (19). In another retrospective study involving 201 patients, the rate of cannulation failure was higher in AVFs that had ipsilateral TVCs (39% vs 11%, P <0.001), whereas the overall AVF survival was longer in the contralateral TVC group (778.7 vs 247.3 days, P <0.002) (9). A third retrospective study of 187 patients, however, showed no difference in assisted (74% vs 64%, P =0.22) and unassisted (62% vs 55%, P =0.41) functional AVF maturation between ipsilateral and contralateral TVC groups (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one previous retrospective study of 322 patients, it was noted that AVF survival was lower in those with ipsilateral TVCs compared with contralateral TVCs, but the primary AVF failure rates were similar (50% vs 53%, P =0.70) (19). In another retrospective study involving 201 patients, the rate of cannulation failure was higher in AVFs that had ipsilateral TVCs (39% vs 11%, P <0.001), whereas the overall AVF survival was longer in the contralateral TVC group (778.7 vs 247.3 days, P <0.002) (9). A third retrospective study of 187 patients, however, showed no difference in assisted (74% vs 64%, P =0.22) and unassisted (62% vs 55%, P =0.41) functional AVF maturation between ipsilateral and contralateral TVC groups (20).…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies have also shown that long-term AVF survival is lower in patients with previous ipsilateral TVC, compared with contralateral TVC (9). However, the effect of an existing TVC and its location on the subsequently formed AVF’s maturation and early function has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of an increased risk of AVF failure in patients with a CVC in this study is consistent with that reported in the Dialysis Outcomes and Practice Patterns Study [42][43][44] . This increased risk may be related to potential hemodynamic effects and central vein stenosis associated with ipsilateral catheter placement 45 . In addition, CVC predispose patients to blood stream infection and hospitalization 46 which could indirectly predispose to AVF failure via hypotension and the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Responsibility for the information and views expressed herein lies entirely with the author(s). Two needles for $50% of hemodialysis over 2-week period Shingarev et al, 2012 (10) Three consecutive hemodialysis sessions (two needles, dialysis blood flow $250 ml/min) Kim et al, 2019 (11) One successful hemodialysis with both cannula Ozpak and Yilmaz, 2019 (12) Four consecutive dialysis sessions AVF, arteriovenous fistula; KHI, Kidney Health Initiative.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Within the TVC group, performance of AVF placed contralateral to TVC was superior to ipsilateral AVF placement, but this effect lost statistical significance by 12 months. Their data suggest that ipsilateral TVC placement is associated with delayed AVF maturation, a divergent finding from previous studies, which showed similar 6-month primary failure rates in these patient groups (10)(11)(12). An important consideration in explaining these differences is the heterogeneity in definitions used when describing successful AVF cannulation or AVF maturation, with Diep et al using the closest definition to the Kidney Health Initiatives' recommendations (Table 2).…”
mentioning
confidence: 91%